A benzimidazole/benzothiazole-based electrochemical chemosensor for nanomolar detection of guanine. Issue 9 (24th December 2014) - Sharma, Hemant; Singh, Narinder; Jang, Doo Ok
Abstract : The electrochemical detection of guanine was accomplished using benzimidazole/benzothiazole-based imine-linked Co(iii ) complexes with platinum electrodes. Abstract : The electrochemical detection of guanine was accomplished using benzimidazole/benzothiazole-based imine-linked Co(iii ) complexes2, 4 and6 with platinum electrodes. Linear sweep voltammetry (LSV), differential pulse voltammetry (DPV) and cyclic voltammetry (CV) were the major analytical techniques used to explore the recognition behavior of the complexes. The detection limit, linear range of detection and sensitivity for complex2 (16.6 nM, 3.5–10 μM and 4.01 μA μM −1 cm 2 ), complex4 (13.4 nM, 5.0–120 μM and 3.18 μA μM −1 cm 2 ) and complex6 (11.3 nM, 2.5–100 μM and 2.0 μA μM −1 cm 2 ) were calculated. Advantages of this methodology include simplicity, an unmodified electrode, high sensitivity and reproducibility.